SYMPTOMATIC INTERARTERIAL COURSE OF CORONARY ARTERIES IN MIDDLE AGED PATIENTS - Abdul Nasir,; Abid Ullah,; Maryum Masoud,; Rafi ullah Jan, (Journal of Ayub Medical College Abbottabad, 2024)
Anomalous aortic origin of a coronary artery (AAOCA) is the most common congenital abnormality and is sometimes associated with various life-threatening conditions. We present the cases of a 35-year-old male and 50 years 50-year-old female with complaints of chest pain. Patients had anomalous aortic origin of coronary arteries with the interarterial course and were treated surgically. By literature review, we came to know that the approach to treat patients with anomalous aortic origin of coronary arteries should be largely individualized and there is no ample scientific data to support any specific diagnostic modality and treatment option.